Low expression Macrophage Migration Inhibitory Factor (MIF) alleles and tuberculosis in HIV infected South Africans. Issue 1 (March 2019) - Reid, Duncan; Shenoi, Sheela; Singh, Ravesh; Wang, Max; Patel, Vinod; Das, Rituparna; Hiramen, Keshni; Moosa, Yunus; Eksteen, Francois; Moll, Anthony P.; Ndung'u, Thumbi; Kasprowicz, Victoria; et al.
Highlights: Low expression MIF alleles are prevalent in South Africa, which has the greatest burden of TB and HIV. Low genotypic MIF expressers were more frequent among HIV cases with TB compared to those without TB. Serum MIF correlated with lower CD4 cells regardless of TB, suggesting HIV impacts MIF expression. Abstract: Host immunity is crucial for controlling M. tuberculosis infection. Functional polymorphisms in the cytokine macrophage migration inhibitory factor (MIF) show global population stratification, with the highest prevalence of low expression MIF alleles found in sub-Saharan Africans, which is a population with the greatest confluence of both TB and HIV infection and disease. We investigated the association between MIF alleles and tuberculosis (TB) and HIV in South Africa. We acquired clinical information and determined the frequency of two MIF promoter variants: a functional −794 CATT5-8 microsatellite and an associated −173 G/C SNP in two HIV-positive cohorts of patients with active laboratory-confirmed TB and in controls without active TB who were all HIV positive. We found a greater frequency of low expression MIF promoter variants (-794 CATT5, 6 ) among TB disease cases compared to controls (OR = 2.03, p = 0.023), supporting a contribution of genetic low MIF expression to the high prevalence of TB in South Africa. Among those with HIV, circulating MIF levels also were associated with lower CD4 cell counts irrespective of TB status (p = 0.016), suggesting an influence of HIV immunosuppression on MIF expression.